ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERATAAN LABA PADA PERUSAHAAN PUBLIK DI INDONESIA - Purwanto, Agus (JURNAL BISNIS STRATEGI, 2004)
Income smoothing is the process of manipulating the time profile of earning reports to make the reported income stream less variable. This study examines the factors that impact income smoothing. Samples in thisstudy are public companies that list in Jakarta Stock Exchange within 2000 - 2003. This research uses 33 public companies which was representative sampel. In this study, there are four independent variables: profitability, size, divident payout ratio, and type of business. Income smoothing will be used as dependent variable. Using descriptive analysis, this study finds that there is 19 companies that practice income smoothing, and 14 companies didn't practice income smoothing. Using munltivariate analysis (logistic regression), with significant level 0,05, there are three independend variables: profitability, divident payout ratio, and type of bussines that significantly influence income smoothing. However, size variable significantly doesn't influence to income smoothing.